An efficient color image encryption scheme based on a matrix scrambling method and a new hybrid chaotic map. Issue 1 (1st January 2021) - Ogras, Hidayet
Abstract: In this paper, an efficient chaos-based image encryption scheme for color images is proposed. This paper includes a strong displacement structure through a specified matrix scrambling method for pixel positions and a new hybrid chaotic map as a key generator for encryption. Chaotic Logistic map is used to generate binary bitstream for controlling diffusion process. The designed map exhibits superior performance in terms of key space range, complexity and chaotic substantiality that enhances security of the whole system. NPCR, UACI, MSE and PSNR values, which are frequently used in performance and security analysis in the field of image encryption, are at a satisfactory level and all parameters have successfully met the necessary conditions. For instance, in a good image encryption algorithm, ideal values of NPCR and UACI parameters should be 99.60% and 33.46%, respectively. The average results obtained in this study are very close to their ideal values as 99.6046 and 33.4733 for NPCR and UACI, respectively. According to a scientific study presented in the similar field, MSE value should be greater than 9, 555; PSNR value must be less than 8.3875. In this study, average MSE and PSNR values calculated for six different test images are 10, 315 and 7.9961, respectively. Some important analysis results have been compared to that of well-known Advanced Encryption Standard (AES) algorithm and a similar study presented in this field. Theoretical analysis and experimental results confirm that the proposed algorithm has great security and effectively encrypts and decrypts the color images with different sizes as well.